Evolution of mammalian sensorimotor cortex: Thalamic projections to parietal cortical areas in Monodelphis domestica - James Clinton Dooley; Joao G. Franca; Adele M. H. Seelke; Adele M. H. Seelke; Dylan Francis Cooke; Dylan Francis Cooke; Leah A. Krubitzer; Leah A. Krubitzer (Frontiers Media S.A., 2015)
The current experiments build upon previous studies designed to reveal the network of parietal cortical areas present in the common mammalian ancestor. Understanding this ancestral network is essential for highlighting the basic somatosensory circuitry present in all mammals, and how this basic plan was modified to generate species specific behaviors. Our animal model, the short-tailed opossum (Monodelphis domestica), is a South American marsupial that has been proposed to have a similar ecological niche and morphology to the earliest common mammalian ancestor. In this investigation, we injected retrograde neuroanatomical tracers into the face and body representations of primary somatosensory cortex (S1), the rostral and caudal somatosensory fields (SR and SC), as well as a multimodal region (MM). Projections from different architectonically defined thalamic nuclei were then quantified. Our results provide further evidence to support the hypothesized basic mammalian plan of thalamic projections to S1, with the lateral and medial ventral posterior thalamic nuclei (VPl and VPm) projecting to S1 body and S1 face, respectively. Additional strong projections are from the medial division of posterior nucleus (Pom). SR receives projections from several midline nuclei, including the medial dorsal, ventral medial nucleus, and Pom. SC and MM show similar patterns of connectivity, with projections from the ventral anterior and ventral lateral nuclei, VPm and VPl, and the entire posterior nucleus (medial and lateral). Notably, MM is distinguished from SC by relatively dense projections from the dorsal division of the lateral geniculate nucleus and pulvinar. We discuss the finding that S1 of the short-tailed opossum has a similar pattern of projections as other marsupials and mammals, but also some distinct projections not present in other mammals. Further we provide additional support for a primitive posterior parietal cortex which receives input from multiple modalities.